Low temperature hermetic laser-assisted glass frit encapsulation of soda-lime glass substrates - Seyedali Emami (2017)
Room temperature and low temperature (120 degrees C) laser-assisted glass frit bonding of soda-lime glass substrates are accomplished in this work. The locally laser melted bonding showed hermeticity with helium leak rate of < 5 x 10(-8) atm cm(3) s(-1), maintaining its leak rate even after standard climatic cycle tests. Small size devices were bonded at room temperature while larger areas were sealed at the process temperature of 120 degrees C. The sealing parameters were optimized through response surface methodology that makes the process capable for further development regardless of device size.